Urban sprawl functional-structural changes in neighborhood settlements: Case of study Shiraz - Musa Kamanroodi Kojuri; KAMRAN Jafarpour Ghalehteimouri; Ali Janbazi; Farhad Azizpour (Indonesian Journal of Geography, 2020)
Sprawl is one of the forms of expansion that has entered the literature of urban management and planning in the last half-century. Iranian cities are very good example for city sprawl and they have experienced this kind of expansion in very short period and very fast. This paper aims to identify, describe, and analyze Shiraz scatter and sprawl development and its resulting functional-structure, this research is based on exploratory, descriptive and analytical methods. Data collection in this research is through the secondary data and fieldwork research techniques. Data analysis demands descriptive and inferential statistics (Pearson regression correlation). This study suggests that since 1952 Shiraz city has experienced rapid growth, continuous and non-continuous. The proportion of scatter and sprawl development with respect to Shiraz expansion increased from 22.02 in 1957-1967 to 72.8 in 1977-2007. There are three period the first rapid development between 1957 and 2967 after that 5 years gap and the next period which is longer from 30 years between 1977 and 2007.  This turning points is in two specific periods are as the result of some consequences: Conversion of agricultural function as a predominant economic function in neighboring communities, into multi-functional agricultural function with emphasis upon services; of some of the rural settlements into Shiraz; The development of extended spatial, administrative, economic, social and structural changes in residential part of Shiraz. Therefore, socioeconomic activities are the main cause of urban sprawl in Shiraz and made Shiraz the most attractive place for in Fars Province. Population growth with correlation between degree of Shiraz scatter development and number of people engaged to service sector by 0.9 has caused a dramatically decline in agriculture (-0.8) and industry (-0.811) sectors. As result rapid urban population growth rate correlation by (0.127) and urbanization coefficient (0.726) and it shows urban and rural migration very important role on scatter development.